Paths to freedom : manumission in the Atlantic world - Brana-Shute, Rosemary, 1944-; Sparks, Randy J. (Carolina lowcountry and the Atlantic world., 2009)
The contributors investigate the cultural consequences of manumission as well as the changing economic conditions that limited the practice by the eighteenth century to understand better the social implications of this multifaceted aspect of the system of slavery.